THE EFFECT OF FRAUD HEXAGON ON FRAUDULENT FINANCIAL STATEMENTS: EMPIRICAL STUDY OF NON-CYCLICALS COMPANIES IN INDONESIA - Mohamad Zulman Hakim; Tariq Tawfeeq Yousif Alabdullah; Mochammad Farid Fadillah; Aisyah Sholikhati; Nurhaliza, Siti; Ika Wulandini (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to analyze the factors of hexagon fraud in detecting financial statement fraud in non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2021. Based on the purposive sampling method, the number of companies sampled in this study was 33 research criteria of non-cyclical companies with a total of 66 observations. The results of this study found that the element of pressure proxied by government projects had a significant effect on fraudulent financial statements. Meanwhile, financial targets, financial stability, changes in directors, ineffective monitoring, change in auditors, frequent number of CEO's pictures, political connections, state-owned enterprises, and audit opinions have no significant effect on fraudulent financial reports in non-cyclicals sector companies listed on the IDX 2020-2021.